Analysis of Korean acne patients according to age groups based on two multicenter studies. Issue 2 (28th October 2016) - Park, Mi Youn; Kim, Kyung Ho; Kang, Hoon; Kye, Young Chul; Kwon, Hyuck Hoon; Kim, Kwang Joong; Kim, Nack In; Kim, Myeung Nam; Ro, Young Suck; Min, Seonguk; Park, Kui Young; Song, Margaret; et al.
Abstract: Along with increasing public concerns on acne and its complications, increasing treatment options seem to lead more acne patients to clinics globally, including Korea. The aim of the present study was to investigate the number and distribution of acne patients according to age group by analyzing number and age of outpatients from several general hospitals in Korea. Two retrospective multicenter studies including 14 general hospitals for a maximum of 10 years were conducted by medical chart review of acne patients. During the last 10 years, total acne patients have increased by 60% in number and patients under the age of 19 years have doubled. Adult acne patients (aged >18 years) accounted for the biggest portion in total acne patients at over 80%. Although upper grade of elementary school patients (aged 10–12 years) accounted for the biggest portion among the childhood acne patients, children under 10 years have also increased rapidly by 73% during the last 10 years. Childhood acne patients (aged <13 years) accounted for 11% of total acne patients. We found that acne patients were increasing consistently and the portion of those aged under 19 years is getting bigger. Additionally, childhood acne patients have increased remarkably.